(untitled) (The Research of Medical Science Review, 2025)
Background: Metabolic syndrome (MetS) is characterized by several lipid and non-lipid factors that collectively contribute to an increased susceptibility to cardiovascular disease. Nonalcoholic fatty liver disease (NAFLD) is common in metabolic syndrome and burgeoning health concern on a global scale and is a contributor to the development of chronic liver disease, Objective: To determine the frequency of metabolic dysfunction-associated steatotic liver disease (MASLD) in patients with metabolic syndrome (MetS) Material & Methods: This was cross sectional study, conducted from 10 August, 2024 to 28 February, 2025, on 149 cases of metabolic syndrome. All the patients would undergo treatment for MetS according to the standard guidelines of management. Presence of MASLD was labeled as per operational definition. Confidentiality of the data was ensured. Results: The study was conducted on 149 cases with metabolic syndrome. In our study, mean age was 47.99 ±4.84 years, mean FBS was 147.83±70.29 mg/dL, mean HbA1c 7.04±1.56%, mean TG level was 204.97±91.50 mg/dL and mean BMI was 28.83±2.86 kg/m2. Mean waist in males was 97.59±4.84 cm and in females was 92.66±6.53 cm. Mean HDL in males was 43.25±5.99 mg/dL and in females was 45.77±5.40 mg/dL. Among all 149 cases, 88 (59.1%) cases were male and 61 (40.9%) cases were female, 89 (59.7%) cases had diabetes and 92 (61.7%) cases were hypertensive. Among all 149 cases of metabolic syndrome, 59 (39.6%) cases were diagnosed with MASLD. Conclusion: In our study, a significant number of cases with metabolic syndrome was also diagnosed with MASLD. So, the authors have concluded that MASLD is a common ongoing ailment in metabolic syndrome. Routine screening for MASLD should be considered as mandatory in workup of cases with metabolic syndrome.